Perceptions and acceptance of yeast-derived dairy in British Columbia, Canada - Powell, Lisa Jordan; Mendly-Zambo, Zsofia; Newman, Lenore Lauri (Frontiers in Sustainable Food Systems, 2023)
Yeast derived-dairy (YDD) produced using cellular agriculture technologies is already available for purchase in the United States, though there has been little study of public understanding of these products. Our pilot study explored consumer perception and acceptance of YDD and yeast-derived agriculture (YDA). The study employed a questionnaire consisting of Likert scale, multiple-choice and open-ended questions, which was disseminated to vegans and the food-interested public in the province of British Columbia, Canada. Quantitative data was analyzed using SPSS 27.0, and qualitative data was collected and analyzed (in English) using thematic analysis. A binary logistic regression model indicated that among our participants, being vegan or 35 years of age or older negatively predicted having positive feelings towards YDA [chi-square (10) = 29.086, p = 0.001]. Vegans were less likely to try or purchase YDD than non-vegans. Consumers in our study shared concerns regarding the health and safety of YDD with many viewing it as non-vegan and a highly processed product. Although vegans receive a disproportionate amount of media attention with regards to cellular agriculture, our pilot study suggests this group may be unlikely to accept or consume YDA or YDD. Rather, our preliminary work indicates non-vegans and individuals under the age of 35 may be a more receptive market. Across groups, confusion about YDA processes may be a barrier to adoption.